PENGEMBANGAN WEBSITE MICROLEARNING INTERAKTIF PADA MATA PELAJARAN IFORMATIKA DI SEKOLAH MENENGAH PERTAMA KELAS VIII DI SMPN 6 GARUT - Putri Liza Anjani; Efi Sofiah; Siti Husnul Bariah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Informatics instruction at SMP Negeri 6 Garut is still dominated by lecture methods and one-way presentation media; consequently, abstract concepts regarding algorithms are difficult for students to grasp, and student engagement remains low. This study aims to develop an interactive microlearning website covering algorithms and programming, determine its feasibility through expert validation, and analyze student responses. The research employs the Research and Development method using the Borg and Gall model, simplified into eight stages: needs analysis, planning, initial product development, expert validation, revision, small-group testing, revision, and large-group testing. The website was developed using native PHP, MySQL, and Bootstrap, featuring three user roles: administrator, teacher, and student. Validation results from subject matter and media experts yielded scores ranging from